INDUKSI PEMBENTUKAN KANTONG DAN PERTUMBUHAN DUA SPESIES TANAMAN KANTONG SEMAR (Nepenthes spp.) PADA BERBAGAI KONSENTRASI MEDIA MS SECARA IN VITRO - Fitri Yelli (JURNAL AGROTROPIKA, 2013)
Nepenthes plant is a unique plant due to its interesting pitcher at the leaf tip. The objective of the research was to determine the suitable MS (Murashige and Skoog) medium concentration for growth of two species of nepenthes and induction pitcher formation.  A factorial experiment arranged in completely randomized design was carried out with the first factor was two species of Nepenthes; N. ampullaria and N. mirabilis.  The second factor was several concentrations of MS medium, i.e.  0.500 MS, 0.250 MS, 0.125 MS, 0.0625 MS and 0.000 MS. The results showed that the number of leaves, the number of pitchers were affected by the type of Nepenthes and MS medium while plant height only affected by type of Nephenthes. N. mirabilis had significance higher number of leaf of 13.47 compared to N. mirabilis of 11.10. However, number of pitchers formed was lower in N. mirabilis compared to N.ampullaria.  Data obtained also showed that the best MS medium for pitcher formation was 0.0625 MS medium.  Keywords : Nepenthes ampullaria, Nepenthes mirabilis, pitcher plant, MS medium